2023
DOI: 10.21873/invivo.13178
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide With Metformin Therapy Ameliorates Hepatic Steatosis and Liver Injury in a Mouse Model of Non-alcoholic Steatohepatitis

Abstract: Background/Aim: Non-alcoholic fatty liver disease is a major cause of liver-related morbidity and mortality. Metformin is a widely used medication and may have additional benefits beyond glycemic control. Liraglutide, a novel treatment for diabetes and obesity, also has beneficial effects on non-alcoholic steatohepatitis (NASH). Metformin and liraglutide have both benefited NASH treatment. However, no study has reported the effects of combination therapy with liraglutide and metformin on NASH. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Besides semaglutide, liraglutide attenuated the gene expression of the lipogenic genes acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS) while mitigating the expression of pro-inflammatory cytokines or transcription factor, including TNF-α and nuclear factor κ-light chain-enhancer of activated B cell (NF-κB) in high-fat diet (HFD) mice with ApoE and adiponectin (Acrp30) knockdown background, thus preventing MASH progression [69]. Consistent with that, Chiu et al showed that treatment with liraglutide-and metformin-induced weight loss, reduced liver/body weight ratio, and ameliorated steatosis, liver injury, and MASH activity in a methionine/choline-deficient (MCD) diet-fed C57BL/6JNarl mouse model [70]. Of note, GLP-1 analogs induce the polarization of macrophages toward the M2 phenotype and, via that, induce the expression of anti-inflammatory molecules such as IL-10, CD163, and CD204 while concurrently reducing c-c motif chemokine ligand 2 (CCL-2) expression [71].…”
Section: Glp-1 Signalingmentioning
confidence: 77%
“…Besides semaglutide, liraglutide attenuated the gene expression of the lipogenic genes acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS) while mitigating the expression of pro-inflammatory cytokines or transcription factor, including TNF-α and nuclear factor κ-light chain-enhancer of activated B cell (NF-κB) in high-fat diet (HFD) mice with ApoE and adiponectin (Acrp30) knockdown background, thus preventing MASH progression [69]. Consistent with that, Chiu et al showed that treatment with liraglutide-and metformin-induced weight loss, reduced liver/body weight ratio, and ameliorated steatosis, liver injury, and MASH activity in a methionine/choline-deficient (MCD) diet-fed C57BL/6JNarl mouse model [70]. Of note, GLP-1 analogs induce the polarization of macrophages toward the M2 phenotype and, via that, induce the expression of anti-inflammatory molecules such as IL-10, CD163, and CD204 while concurrently reducing c-c motif chemokine ligand 2 (CCL-2) expression [71].…”
Section: Glp-1 Signalingmentioning
confidence: 77%
“…P<0.05 was considered to indicate a statistically significant difference. Statistical analyses were performed using SPSS ( ; version 22) and R (version R 4.1.0) software ( 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the differences between two and multiple groups, SPSS version 25.0 (IBM, Corp.) was used to perform a one-way analysis of difference, followed by Dunnett’s test and Tukey’s post-hoc test. A statistically significant difference was defined as one with a P value of 0.05 [ 40 ].…”
Section: Methodsmentioning
confidence: 99%